Carbon quantum dots nanoparticles deteriorate the antioxidant cellular status and stimulate DNA damage in tissues of the house fly Musca domestica larvae. Issue 1 (31st December 2023) - Ragheb, Mona; Shalaby, Afaf A.; El-Sharkawy, Heba M.
ABSTRACT: The house fly Musca domestica, the medical pest is a vector of many pathogenic organisms, that had showed insecticide resistance against popular active chemical ingredients, which represents a global issue that hinders successful insect control. This study aimed at investigating the effect of carbon quantum dot nanoparticles (CQDNPs) on some biochemical and cellular parameters in cells of the house fly larvae. In this study, serial concentrations of CQDNPs were tested against the house fly larvae. For each concentration, four replicates of third instar larvae of Musca domestica (twenty-five larvae for each one) were involved. Control groups were regarded by adding plain dechlorinated water to the larval medium. The LC50 of CQDNPs on the house fly larvae was determined after 24 hours of incubation. Levels of total protein and albumin were inspected along with the levels of antioxidant enzymes regarding superoxide dismutase, catalase and glutathione reductase and enzymes of oxidative stress regarding lipid peroxidase and nitric oxide. Moreover, comet assay was performed in tissues of the treated larvae. Results revealed that the LC50 (3.19 mg/ml) showed significant decrease in the total protein and albumin levels. Further, significant decrease in the activities of the antioxidant enzymes was implied along with significant increase of cellular damage enzymes in tissues of the treated larvae. Eventually, DNA damage was detected implying the larvicidal potency of carbon quantum dots against the house fly larvae. To conclude, CQDNPs exhibit insecticidal potency against the house fly larvae regarding cellular and molecular aspects.